Building Africa´s Confidence and Scientific Capacity to Manage Modern Biotechnology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
African policy-makers are increasingly confronted with a growing range of complex scientific, and ethical issues associated with the development and use of genetically modified products from modern biotechnology. They are under increasing pressure to pron